2008
DOI: 10.1039/b807914e
|View full text |Cite
|
Sign up to set email alerts
|

Engineered biosynthesis of hybrid macrolide polyketides containing d-angolosamine and d-mycaminose moieties

Abstract: The glycosylation of natural product scaffolds with highly modified deoxysugars is often essential for their biological activity, being responsible for specific contacts to molecular targets and significantly affecting their pharmacokinetic properties. In order to provide tools for the targeted alteration of natural product glycosylation patterns, significant strides have been made to understand the biosynthesis of activated deoxysugars and their transfer. We report here efforts towards the production of plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
1
36
0
2
Order By: Relevance
“…37 Accordingly, dTDP-D-mycaminose is a deoxyaminosugar that contains a core aglycone of polyketide origin, with a deoxysugar moiety attached. 38 The union of the deoxysugar moiety has been reported to be essential for the bioactivities of these bacterial products, including antibacterial and anti-inflammatory effects. 39,40 Our group previously demonstrated that quercetin supplementation, but especially the combined administration of trans-resveratrol and quercetin, increased the abundance of the bacterium Clostridium methylpentosum when compared to the HFS diet-fed reference group.…”
Section: Discussionmentioning
confidence: 99%
“…37 Accordingly, dTDP-D-mycaminose is a deoxyaminosugar that contains a core aglycone of polyketide origin, with a deoxysugar moiety attached. 38 The union of the deoxysugar moiety has been reported to be essential for the bioactivities of these bacterial products, including antibacterial and anti-inflammatory effects. 39,40 Our group previously demonstrated that quercetin supplementation, but especially the combined administration of trans-resveratrol and quercetin, increased the abundance of the bacterium Clostridium methylpentosum when compared to the HFS diet-fed reference group.…”
Section: Discussionmentioning
confidence: 99%
“…The primers were designed from two conserved regions of deduced amino acid sequences of P450s implicated in formylation of 16-member macrolides (4)(5)(6)(7)(8). The complete nucleotide sequence of the rosamicin biosynthetic gene cluster in Micromonospora carbonacea subsp.…”
mentioning
confidence: 99%
“…In principle, 2′-deoxy amphotericin B could be generated by biosynthetic engineering. An activated 2′-deoxymycosamine could be synthesised in vivo using genes for TDP-Dangolosamine formation (Schell et al, 2008). However, current knowledge of polyene GTs indicates that redesigning them to accept alternative dTDP-sugars could prove challenging.…”
Section: Glycosylationmentioning
confidence: 99%